Análise elastoplástica da propagação de trincas pelo método dos elementos de contorno - Marcelo Claudio Teixeira (2006)
The present work describes the formulation and numerical implementation of twodimensional Dual Boundary Element Method to the analysis of elastoplastic fracture mechanics and its application to the fatigue crack growth. The dual equations of the method are the displacement and the traction boundary integral equations. When thedisplacement equation is applied on one of the crack surfaces and the traction equation on the other, general mixed-mode crack problems can be solved with a single-region formulation. In order to avoid collocation at crack tips, crack kinks and crack-edge corners, both crack surfaces are discretized with discontinuous quadratic boundary elements.Several yield criteria in a unified form are used in association with the initial stress process to simulate the plastic behaviour, in a non-linear algorithm which does not include the assumption of incompressibility of the inelastic strain. The region expected to yield is discretized with internal quadratic triangular cells with flat sides. The computation of the domain integrals is carried out by a semi-analytical integration scheme. The path-independent integral, the J-Integral, is used for evaluation of stress intensity factor. The calculation is straightforward, because chosen path is coincident with points in grid cells. Different crack examples are presented to validate the procedure and the inelastic material behavior influence in the stress intensity factor value is compared with elastic and inelastic results found in the technical literature.